2009
DOI: 10.1002/jbm.a.32432
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of the femoral cortex due to age‐, sex‐, and endoprosthetic‐related effects emphasized by osteonal dimensions and remodeling

Abstract: Cortical remodeling is of particular importance to femoral strength. However, osteonal morphology and its quantitative changes are still poorly understood. Therefore, osteons as the cortexes basic structural units should serve for histomorphometrical assessment of reorganization mechanisms. Total hip replacement (THR) cases as well as relevant controls were investigated to gain insight into changes within stress shielded as well as age- and sex-associated bone with emphasis on the underlying osseous cell inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 44 publications
4
29
0
2
Order By: Relevance
“…Fig. 4 demonstrates the dramatically higher number of osteons in aged bone; in fact, the aged sample has nearly three times the osteonal density, defined as the number of osteons per unit bone area, consistent with reports elsewhere (24). The higher osteon density in aged bone supports the notion that a growing crack will have more cement lines at which microcracks can form, resulting in both smaller crack bridges and a lower crack-growth toughness.…”
Section: Resultssupporting
confidence: 86%
“…Fig. 4 demonstrates the dramatically higher number of osteons in aged bone; in fact, the aged sample has nearly three times the osteonal density, defined as the number of osteons per unit bone area, consistent with reports elsewhere (24). The higher osteon density in aged bone supports the notion that a growing crack will have more cement lines at which microcracks can form, resulting in both smaller crack bridges and a lower crack-growth toughness.…”
Section: Resultssupporting
confidence: 86%
“…and similar rate of mineral deposition at the surface~Sahoo et al, 2006!. That is, as portrayed in experimental studies in materials science that the PSD slopes depended on the rate of particle deposition on the surface, slow surface deposition rate of the material would result in smooth and less complex surface morphology~lower roughness, lower FD; Sahoo et al, 2006!. Apart from the size of mineral crystals, which was linked to bone tissue age in several studies of cortical and trabecular bone~Su et al, 2003;Kuhn et al, 2008;Milovanovic et al, 2011!, the degree of matrix mineralization, which can be expressed in the form of Ca/P ratio, has also been regarded as an indicator of bone age~Legros et al., 1987;Grynpas, 1993;Skedros et al, 1993;Huja et al, 2006;Kuhn et al, 2008;Roschger et al, 2008;Busse et al, 2009Busse et al, , 2010aBusse et al, , 2010b Our spectroscopy analysis showed consistent Ca/P ratio between the groups. Therefore, two independent measures of bone tissue age in our study~crystal size and degree of mineralization!…”
Section: Femoral Neck Outer Diametersupporting
confidence: 80%
“…The results demonstrated that the senior group had the higher porosity area and lower osteon area than the young group [4].…”
Section: Resultsmentioning
confidence: 90%